2011
DOI: 10.1115/1.4002698
|View full text |Cite
|
Sign up to set email alerts
|

A Microstructurally Driven Model for Pulmonary Artery Tissue

Abstract: A new constitutive model for elastic, proximal pulmonary artery tissue is presented here, called the Total Crimped Fiber Model. This model is based on the material and micro-structural properties of the two main, passive, load-bearing components of the artery wall, elastin and collagen. Elastin matrix proteins are modeled with an orthotropic neo-Hookean material. High stretch behavior is governed by an orthotropic crimped fiber material, modeled as a planar sinusoidal linear elastic beam, which represents coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Later, Sacks demonstrated that with the use of only an equi-biaxial test and the experimentally measured fiber orientation distribution, the complete in-plane biaxial response could be simulated (Sacks, 2003). More recently, structural approaches have been used for a wide range of native and engineered tissue applications, such as elastomeric tissue engineering scaffolds (Courtney et al, 2006), urinary bladder wall (Wognum et al, 2009), and many others (Fata et al, 2014; Hansen et al, 2009; Hollander et al, 2011; Kao et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Later, Sacks demonstrated that with the use of only an equi-biaxial test and the experimentally measured fiber orientation distribution, the complete in-plane biaxial response could be simulated (Sacks, 2003). More recently, structural approaches have been used for a wide range of native and engineered tissue applications, such as elastomeric tissue engineering scaffolds (Courtney et al, 2006), urinary bladder wall (Wognum et al, 2009), and many others (Fata et al, 2014; Hansen et al, 2009; Hollander et al, 2011; Kao et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we have neither mechanical data nor three-dimensional microscopic images directly showing collagen fibers’ two-dimensional behavior. Nevertheless, previous studies have suggested that collagen fibers have a planar distribution in human cerebral arteries, calf proximal PAs and rabbit carotid arteries [21,6062], and several modeling studies have adopted a planar distribution of collagen fibers previously with good results [26,35,41]. The zero value for the material parameter, C r , is thus believed to be reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that PA is stiffer in the circumferential direction than all other directions in this circumferential-longitudinal plane if all the collagen fibers have exactly the same mechanical properties and that the parameter C θ should be larger than C z . Nevertheless, previous modeling studies on calf and rat proximal PAs suggested nearly transversely isotropic behavior [21]. Since axial force-length data were not available, we assumed that the PA is transversely isotropic, i.e., the mechanical properties in the circumferential and longitudinal directions are the same, which forces the parameters C θ = C z .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations